2011
DOI: 10.1021/ja204856a
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Electron Demand Diels–Alder Reactions of 1,2,3-Triazines: Pronounced Substituent Effects on Reactivity and Cycloaddition Scope

Abstract: A systematic study of the inverse electron demand Diels–Alder reactions of 1,2,3-triazines is disclosed, including an examination of the impact of a C5 substituent. Such substituents were found to exhibit a remarkable impact on the cycloaddition reactivity of the 1,2,3-triazine without altering, and perhaps even enhancing, the intrinsic cycloaddition regioselectivity. The study revealed that not only may the reactivity be predictably modulated by a C5 substituent (R = CO2Me > Ph > H), but that the impact is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 122 publications
1
99
0
1
Order By: Relevance
“…The potential of this reaction was extensively studied by Boger and others . The group of Boger showed, for instance, that tetrazines and triazines are, in particular, excellent dienes reacting with a wide range of different dienophiles . The reason for this behavior is the electron‐poor structure and the release of nitrogen as the thermodynamic driving force.…”
Section: Bidentate Lewis Acid Catalysis By the Activation Of The Starmentioning
confidence: 99%
“…The potential of this reaction was extensively studied by Boger and others . The group of Boger showed, for instance, that tetrazines and triazines are, in particular, excellent dienes reacting with a wide range of different dienophiles . The reason for this behavior is the electron‐poor structure and the release of nitrogen as the thermodynamic driving force.…”
Section: Bidentate Lewis Acid Catalysis By the Activation Of The Starmentioning
confidence: 99%
“…[24][25][26][27][28][29] Boger further showed that 1,2,3-triazines react with electron-rich dienophiles. 30 To compare the intrinsic DA reactivities of 1,2,3-and 1,2,4-triazines with that of 1,2,4,5-tetrazine, we evaluated the activation free energies for their reactions with ethylene by density functional theory (DFT) calculations ( Figure 1A, Table S1). [31][32][33] The computational analysis suggested that 1,2,4-triazine is much more reactive than 1,2,3-triazine (activation free energy: 29.3 versus 41.0 kcal/mol), but less reactive than 1,2,4,5-tetrazine (29.3 versus 21.9 kcal/mol).…”
mentioning
confidence: 99%
“…The pioneering work dealing with this so-called Carboni-Lindsey reaction has been reviewed by Boger [265]. Triazine and tetrazine derivatives are commonly used as commercial dyes [266], as insecticides [267] and more recently as pharmaceutical agents (Figure 17) [268,269].…”
Section: Six-membered Heterocycles With Three or Four Nitrogen: Triazmentioning
confidence: 99%